“You're made to feel like you're the crazy one”: an interpretive description of former college student-athletes’ views of emotional abuse - Adams, Kat V.; Alexander, Katherine N.; Dorsch, Travis E. (Frontiers in Sports and Active Living, 2024)
Many normalized coaching behaviors are often abusive yet are seen by coaches and athletes as instrumental in achievement and competition. The current study was designed to extend past research and theory by subjectively exploring how and why former intercollegiate athletes identified their head coach as emotionally abusive. Twenty former intercollegiate student-athletes (Mage = 26.0 years) from nine sports participated in semi-structured interviews ranging from 65 to 189 min (M = 105.8, SD = 58). Interpretive description methodology was used with reflexive thematic analysis to generate a coherent conceptual description of the themes and shared experiences that characterized emotionally abusive coaching. The themes that associated with an athlete labeling a coach as emotionally abusive fall under two aspects of Stirling and Kerr's 2008 definition: non-contact coach behaviors and the resulting harmful outcomes experienced by the athletes. Non-contact behaviors were ones that diminished performance, neglected holistic development, and were inconsistent. The harmful effects were the negative emotional responses and dehumanization experienced by athletes. Finally, participants felt that a coach's desire for power and control over athletes explained the coach's behaviors generally. Based on these results, we put forth the conceptual claim that emotional abuse, and psychological violence more broadly, cannot be defined or identified based solely on the perpetrator's behaviors. The athlete's cognitions, perceptions, emotions, and behaviors are critical in determining whether emotional abuse occurred, and these interpretations are shaped by an athlete's existing relationship with the coach.